Genetic organization of the psbAD region in phages infecting marine Synechococcus strains - Millard, Andrew (National Academy of Sciences, 2004)
The discovery of the genes psbA and psbD, encoding the D1 and D2 core components of the photosynthetic reaction center PSII (photosystem II), in the genome of the bacteriophage S-PM2 (a cyanomyovirus) that infects marine cyanobacteria begs the question as to how these genes were acquired. In an attempt to answer this question, it was established that the occurrence of the genes is widespread among marine cyanomyovirus isolates and may even extend to podoviruses. The phage psbA genes fall into a clade that includes the psbA genes from their potential Synechococcus and Prochlorococcus hosts, and thus, this phylogenetic analysis provides evidence to support the idea of the acquisition of these genes by horizontal gene transfer from their cyanobacterial hosts. However, the phage psbA genes form distinct subclades within this lineage, which suggests that their acquisition was not very recent. The psbA genes of two phages contain identical 212-bp insertions that exhibit all of the canonical structural features of a group I self-splicing intron. The different patterns of genetic organization of the psbAD region are consistent with the idea that the psbA and psbD genes were acquired more than once by cyanomyoviruses and that their horizontal transfer between phages via a common phage gene pool, as part of mobile genetic modules, may be a continuing process. In addition, genes were discovered encoding a high-light inducible protein and a putative key enzyme of dark metabolism, transaldolase, extending the areas of host-cell metabolism that may be affected by phage infection.